Anti-NMDAR encephalitis in a 19 year old female patient with ovarian teratoma: A case report. (July 2021) - El Hanna, Johnny; Quenum, Codjo; Arsalane, Abdelilah
Abstract: Background: Anti -N- Methyl-d -Aspartate encephalitis is a subcategory of auto-immune encephalitis. It is known for its aggressive presenting symptoms and rapid deterioration, yet it is treatment responsive. It is associated in 50 % to ovarian teratoma. Case: We report the case of a 19 year old female patient presenting for a psychiatric disorder of sudden onset with rapid deterioration. Neurologic imaging was in favor of encephalitis, and CSF studies revealed Anti NMDA receptors. Further abdominal imaging showed a right ovarian teratoma of 4 cm. Laparoscopic ovarian cyst resection was done, and corticotherapy, IVIG and anticonvulsants were given. We report complete resolution of symptoms after 7 months. Conclusion: Anti-NMDA receptor encephalitis with ovarian teratoma is a rare entity with rapid deterioration. Early diagnosis, surgical resection and proper medical treatment are essential for the management of this disease.